2019
DOI: 10.1038/s41598-019-49239-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain responses to social punishment: a meta-analysis

Abstract: Many studies suggest that social punishment is beneficial for cooperation and consequently maintaining the social norms in society. Neuroimaging and brain stimulation studies show that the brain regions which respond to violations of social norms, the understanding of the mind of others and the executive functions, are involved during social punishment. Despite the rising number of studies on social punishment, the concordant map of activations - the set of key regions responsible for the general brain respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…In the last decade, there has been an increasing interest in these issues, while great developments have taken place, thanks to functional neuroimaging techniques (de Quervain et al, 2004 ; Buckholtz and Marois, 2012 ; Yang et al, 2019 ; Zinchenko, 2019 ).…”
Section: Altruistic Punishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, there has been an increasing interest in these issues, while great developments have taken place, thanks to functional neuroimaging techniques (de Quervain et al, 2004 ; Buckholtz and Marois, 2012 ; Yang et al, 2019 ; Zinchenko, 2019 ).…”
Section: Altruistic Punishmentmentioning
confidence: 99%
“…The reward system is a group of neural structures responsible for motivation, associative learning, and positive emotions, especially those involving pleasure as a fundamental component. The thalamus, dorsolateral prefrontal cortex (DLPFC), nucleus accumbens, anterior cingulate cortex (ACC), insula, and caudate nucleus are considered to be part of this neural system (Sanfey et al, 2003;de Quervain et al, 2004;King-Casas et al, 2005;Strobel et al, 2011;Buckholtz and Marois, 2012;Morese et al, 2016;Zinchenko, 2019). Haber et al (2006) highlighted the mediation of DLPFC and caudate in punishment responses, being these hubs involved in directing attention toward relevant stimuli, or in understanding communication intentions between individuals.…”
Section: Altruistic Punishment and Reward Systemmentioning
confidence: 99%
“…Altruistic SPP can be observed if economic self-interest is overridden and unfair offers are rejected, via activation of System 1, for evaluation of the norm violation, of the dACC/aMCC, to encode and signal the conflict with self-interest and of the right dlPFC, to suppress self-interest in order to punish. This network model is partially supported by the meta-analytical findings of Zinchenko (2019). The authors reported convergent bilateral activation in the anterior insula and left superior frontal gyrus (SFG, corresponding broadly to the dlPFC), areas related to salience and central-executive networks.…”
mentioning
confidence: 61%
“…Crucially, dACC/aMCC involvement was reported in previous meta-analyses (Feng et al, 2015;Gabay et al, 2014), but not by Zinchenko (2019). This might be due to the heterogeneity of the studies that were included in the meta-analysis and did not always involve resolving a cognitive conflict (UG, third-party punishment game, criminal scenarios evaluation, and social rejection tasks).…”
Section: Discussionmentioning
confidence: 89%
“…Within the social-affective topics, social cognition, rather than affect (28) or traditional moral judgment (29), explains more of the variation. This contrasts with previous studies of the neural correlates of social punishment (30)(31)(32)(33)(34)(35) and judgment bias (36). We have operationalized crime-type bias as the component of case strength ratings for each scenario that correlates with punishment (Fig.…”
Section: Main Textmentioning
confidence: 84%